2015
DOI: 10.1097/aap.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Waveform Analysis as an Adjunct to Loss of Resistance for Thoracic Epidural Blocks

Abstract: Epidural waveform analysis (with pressure transduction through the needle) provides a simple adjunct to LOR for thoracic epidural blocks. Although its use was devoid of complications, further confirmatory studies are required before its routine implementation in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 12 publications
3
41
1
Order By: Relevance
“…In this observational trial of lumbar epidural analgesia, pressure waveform analysis through the epidural needle resulted in a higher sensitivity and positive predictive value than noted previously for thoracic epidural placement (91.1% and 94.9%, respectively), but a lower specificity and negative predictive value (83.8% and 73.8%, respectively) [10]. However, this should be interpreted with caution, as an unexpectedly low failure rate [1] of 3% means that the calculations of specificity and negative predictive values are derived from just a few individuals.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…In this observational trial of lumbar epidural analgesia, pressure waveform analysis through the epidural needle resulted in a higher sensitivity and positive predictive value than noted previously for thoracic epidural placement (91.1% and 94.9%, respectively), but a lower specificity and negative predictive value (83.8% and 73.8%, respectively) [10]. However, this should be interpreted with caution, as an unexpectedly low failure rate [1] of 3% means that the calculations of specificity and negative predictive values are derived from just a few individuals.…”
Section: Discussionmentioning
confidence: 74%
“…Pressure waveform analysis provides a simple confirmatory adjunct to loss-of-resistance; when the needle (or catheter) is correctly positioned inside the epidural space, a pulsatile waveform synchronised with arterial pulsations will be seen [2]. In a recent trial of 160 patients having thoracic epidural placement, we observed 91% sensitivity and 84% specificity when waveform analysis was used to verify the correct placement of the epidural needle [10]. Subsequently, in a study involving two academic centres, we demonstrated that thoracic epidural needle placement using loss-of-resistance, confirmed with pressure waveform analysis, was associated with a 2% failure rate compared with 24% for loss-of-resistance alone (p = 0.002) [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations